Selective continuous flow synthesis of hydroxy lactones from alkenoic acids. Issue 4 (19th July 2017) - Cerra, Bruno; Mangiavacchi, Francesca; Santi, Claudio; Lozza, Anna Maria; Gioiello, Antimo
Abstract : The first in-flow selenium-mediated catalysis has been realized under eco-friendly conditions to convert alkenoic acids into hydroxy lactones with a high regio- and diastereo-selectivity ratio. Abstract : A novel approach to synthesize hydroxy lactones using flow chemistry is reported. The system could be applied to a variety of functionalized alkenoic acids allowing the simple and eco-friendly generation of lactonic products within one hour (50 min). The reaction was optimized in terms of efficiency, productivity, resources and eco-sustainability using an integrated flow process assisted by in-line work-up and purification. In one example, the method was scaled to deliver 22 mmol of the product.